ANALISIS PROMOSI DESTINASI DESA WISATA KOTO SENTAJO KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Rochim, Abdul; Yulia, Nur Arini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Tourism is a vital sector that can enhance local economies through the development of regional potential. This research aims to analyze the marketing situation of the Koto Sentajo Tourism Village in Kuantan Singingi Regency, Riau Province. This village is known for its rich cultural and historical heritage, including traditional houses established as early as the 18th century and enduring customary tribal traditions. The study employs a descriptive qualitative approach, utilizing observation, interviews, and documentation techniques. The findings reveal that although Koto Sentajo has strong potential as a cultural and natural tourism destination, current marketing strategies remain suboptimal. Promotional efforts are mostly limited to specific events, with uneven distribution of information due to budget constraints. Community participation and the application of Community-Based Tourism (CBT) principles are essential to sustainable tourism development and increasing visitor interest. This study is expected to serve as an evaluation tool and provide insights for destination managers and local governments to strengthen tourism village marketing strategies. Keywords: "Promotion of Tourism Village, Koto Sentajo Traditional Village, Cultural Tourism, promotional challenges."